Flap endonuclease 1 and DNA-PKcs synergistically participate in stabilizing replication fork to encounter replication stress in glioma cells - Jing Zhang; Mu Chen; Ying Pang; Meng Cheng; Bingsong Huang; Siyi Xu; Min Liu; Hao Lian; Chunlong Zhong (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Selectively utilizing alternative mechanisms to repair damaged DNA in essential factors deficient cancer facilitates tumor genetic evolution and contributes to treatment resistance. Synthetic lethality strategies provide a novel scenario to anticancer therapy with DNA repair protein mutation, such as glioma with DNA-PKcs-deficiency, a core factor crucial for non-homologous end joining (NHEJ) mediated DNA damage repair. Nevertheless, the clinical significance and molecular mechanisms of synthetic lethality function by interfering tumor DNA replication remain largely unexplored. Methods Cancer clinic treatment resistance-related replication core factors were identified through bioinformatics analysis and RNA-sequencing and verified in clinical specimens by immunoblotting and in situ Proximity Ligation Analysis (PLA). Then, in vitro and in vivo experiments, including visible single molecular tracking system were performed to determine functional roles, the molecular mechanisms and clinical significance of synthetic lethality on glioma tumors. Results Hyperactive DNA replication and regulator Flap endonuclease 1 (FEN1) provides high efficiency DNA double strand breaks (DSB) repair abilities preventing replication forks collapse during DNA replication which facilitate adaptation to selective pressures. DNA-PKcs deficient glioma cells are highly dependent on FEN1/BRCA1/RAD51 to survival and counteract replication stress. FEN1 protects perturbed forks from erroneous over-resection by MRE11 through regulating of BRCA1-RAD51 and WRN helicase, uncovering an essential genetic interaction between FEN1 and DNA-PKcs in mitigating replication-stress induced tumor genomic instability. Therapeutically, genetic depletion or molecular inhibition of FEN1 and DNA-PKcs perturb glioma progression. Conclusions Our findings highlight an unanticipated synthetic interaction between FEN1/BRCA1/RAD51 and DNA-PKcs when dysfunction leads to incompatible with cell survival under conditions of interrupted replication progression by disrupting addictive alternative tumor evolution and demonstrate the applicability of combined FEN1 and DNA-PKcs targeting in the treatment of glioma.